SINTESIS DAN KARAKTERISASI SUPERKONDUKTOR SENYAWA TEMBAGA OKSIDA BERBASIS BISMUTH DAN BERFASE- 1212 - Hikmawati, Dyah
Abstract: An experiment has been carried out on the synthesis of 4 different Bi based 1212 systems by means of solid state reaction. The purpose of this experiment is to produce the 1212 system with different thickness of the conducting layer and different interlayer separations which could be used for a study on the interlaycr tunneling theory (IL'l') of Anderson. The highest phase purity -99% and largest grain were obtained on the samples of [(Bi1-x Mox)o.33 Cuo.6, JSrz Cu2 Oy which was not superconducting before any further treatment. Some indication of resistive transition was observed after 20 hours of annealing in oxygen. Further annealing may be needed before a definite conclusion can be made on the superconductive transition. On the other hand, the sample of initial molar composition (Bioo4o Pbe.35) Sr2 (CaO., Yo3) Cuzco Qy exhibited superconducting transition at 87 K and 101 K for a volume fraction of 48% and 53%, respectively. As the samples still feature relatively abundant volume fraction component of 21% and 37% of 2212 phase, the superconductive transition may well be attributed to this well-known phase. The other two samples each with an initial molar composition (Bio.ss-x Pb,,) Sr2 (Cao.4 Yo,7) Cuz., Oy with x = 0.55 and (Bio.4o Pb,) o.5Sr2 (Cad-X Y,J Cu2.05 Oy with x = 0.40 did not exhibit superconductivity transition for a volume fraction of 92% and 62 %, respectively. It is concluded therefore that further experiment should be carried out with wider range of compositional variation as well as longer annealing process before a conclusive evaluation can be made on these systems.